2013
DOI: 10.1007/s10909-013-0984-5
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the Optical Performance of Prototype TES Bolometers for SAFARI

Abstract: We have measured the optical response of prototype detectors for SAFARI , the far-infrared imaging spectrometer for the SPICA satellite. SAFARI's three bolometer arrays, coupled with a Fourier transform spectrometer, will provide images of a 2 × 2 field of view with spectral information over the wavelength range 34-210 µm. Each horn-coupled bolometer consists of a transition edge sensor (TES), with a transition temperature close to 100 mK, and a thin-film Ta absorber on a thermally-isolated silicon nitride mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The highly sensitive TES, which is coupled to the Ta absorber then detects the minute increase in temperature due to the signal absorbed by the Ta. Inevitably some level of signal will be returned back through the waveguide feed, and some will be lost through the free-space gap (if present) between the waveguide and cavitybackshort, as is the case with the current design used in the TES testbed [12]. The purpose of the free-space gap is to allow some distance between the delicate TES array chip and the metal block that contains the feed horn array, as vibrations during launch could cause damage if the two were to come into contact.…”
Section: Purpose Of Cavity and Backshortmentioning
confidence: 99%
“…The highly sensitive TES, which is coupled to the Ta absorber then detects the minute increase in temperature due to the signal absorbed by the Ta. Inevitably some level of signal will be returned back through the waveguide feed, and some will be lost through the free-space gap (if present) between the waveguide and cavitybackshort, as is the case with the current design used in the TES testbed [12]. The purpose of the free-space gap is to allow some distance between the delicate TES array chip and the metal block that contains the feed horn array, as vibrations during launch could cause damage if the two were to come into contact.…”
Section: Purpose Of Cavity and Backshortmentioning
confidence: 99%
“…As can be seen in Figure 2, there is a gap between the exit aperture of the horn and the TES detector. We modified the horn plate to reduce this gap from 230 to 50 µm and found that the detected power increased significantly 29 . This is expected 20 and can be understood intuitively in terms of a reduction of the power lost to the sides.…”
Section: Measurementsmentioning
confidence: 99%
“…We have previously estimated optical efficiencies of 88% under the assumption of a single mode propagating in the feedhorn 5 . These measurements were with a large illuminator aperture so that the beam of the horn was fully illuminated.…”
Section: Optical Efficiency Measurementsmentioning
confidence: 99%